Introduction to the Special Issue - Lorenzo-Gomez, J. Daniel; Núñez-Cacho, Pedro; De Massis, Alfredo; Kotlar, Josip (European Journal of Family Business, 2020)
Innovation in family firms is still a controversial issue within the academic community and poses some unique challenges for family business owners and managers. This special issue on innovation in family firms results from the cooperation of both academic and business guest editors, in a pioneering initiative that is not usual in academic journals. Indeed, a key feature of this Special Issue has been the collaboration with two family business leaders, who have been involved in the editorial process together with the academics. The two business editors that we involved are Antonio Gallardo, Vicepresident of Almirall and former director of FBN-Family Business Network, and Ignacio Osborne, CEO of the Osborne Group and Chairman of the Spanish Family Firm Institute. In order to introduce the six papers that make up this special issue on innovation in family firms, we as academic editors are pleased to include some comments from the business editors that emerged during our interactions with the aim to make a step forward toward bridging the gap between research and practice on family business innovation, acknowledging the different perspectives and approaches adopted by academics and practitioners. As the business editor Mr. Osborne points: “Innovation issues in family firms are nowadays more important than ever, due to the rapid developments that are occurring in the business world and its corresponding technologies”. Despite being a topic analyzed by a number of authors over time (Feranita, Kotlar and De Massis, 2017; Aparicio, Iturralde and Sánchez-Famoso, 2020 in this issue; Chrisman, Chua, De Massis, Frattini and Wright, 2015), the study of innovation in family business still requires a greater volume of research to provide answers to the needs of family businesses. The distinctive nature of family firms results in a complex influence on the innovation process (De Massis, Frattini and Lichtenthaler, 2013), which is reflected in mixed research findings. For instance, the conclusions of the published research offer sometimes contradictory results, since family businesses can be considered innovative (Aronoff, 1998; Craig and Moores, 2006) or conservative (Sharma, Chrisman, y Chua, 1997; Zahra, Hayton y Salvato, 2004; Gómez-Mejía et al., 2007), with several studies that can support whatever of the two options. Family businesses present a number of characteristics that, a priori, seem to favor innovation, such as long-term orientation (Tagiuri and Davis, 1996; Ward and Aronoff, 1994), the desire for continuity through the following generations (Miroshnychenko et al., 2020; Gallo, 1995), patient capital (De Massis, Audretsch, Uhlaner and Kammerlander, 2018; Sirmon and Hitt, 2003), and the long tenure of their main leaders (Lorenzo, 2020). The replacement of the prior generation by the next generation implies the access of younger people to the leadership of the company, who also often present a greater level of qualification (De Massis et al., 2008; Cabrera-Suárez, 2011). Young and qualified leaders would provide a new momentum to the firm, by means of the renewal of the firm (Núñez-Cacho and Lorenzo, 2020). Likewise, the successors receive an important legacy by means of the values of the family business (Erdogan et al., 2020), such as effort, perseverance, austerity, excellence, long-term orientation and entrepreneurial spirit, as basic foundations of their way of understanding business activity (Bermejo, 2008). Accordingly, the new generation managers could be in the best conditions to reinvent the company, since they know the business from within and they also provide the new vision of a person with a working life ahead. Another factor that favors the renewal impulse of the next generation is the familial support to carry out a prolonged tenure over time, which will not be as conditioned by short-term results as in other types of companies, by the so-called patient capital (Sirmon and Hitt, 2003) of the family business (Lorenzo, 2020). But, even if these ideal conditions are met in a specific family firm, it is not guaranteed that the company realizes the innovation it needs. Therefore, it is needed to shed more light about the determinants and conditions for innovation. The editors of this special issue selected a number of papers to reflect the state-of-the-art on this topic, indicating some of the most promising research lines on innovation. According to the business editor Mr. Gallardo, “A very important aspect emerging from this special issue is that the papers published in it reveal that external contributions to the internal know-how of the family and the business are often vital to help produce the changes needed by a family firm for innovation to take place”. Innovation in the family business has been a phenomenon of great interest to researchers, especially in the last decade. This is highlighted in the article that opens this special issue by presenting a complete bibliometric review of the literature on innovation in family businesses. Generally, researchers have noted that the influence of the family is the factor that makes this type of businesses different from the other ones (Habbershon and Williams, 1999; Lorenzo and Núñez-Cacho, 2012). However, in order to conclude that this is really true, it is necessary to identify the nature of these differences and determine how and why they affect the innovative behavior of the family business. The paper Innovation on family businesses: A holistic bibliometric(Aparicio, Iturralde and Sánchez-Famoso, 2020) offers an overview of the research field through an analysis of 207 articles that were published between 1994 and 2017. The authors complement other recent reviews such as those by Feranita, Kotlar and De Massis (2017) and Calabrò, Vecchiarini, Gast, Campopiano, De Massis and Kraus (2019), and reflect about the take-off of research on innovation that takes place since 2009. In the study two differentiated periods are highlighted: An initial one that covers the years 1994 to 2009, and one of expansion from 2010 to 2017. In addition, they identify the most influential journals, the most referenced articles, the most productive scholars -namely, De Massis, Frattini, Craig, Chrisman, Fang, Kotlar and Nordqvist appear as the most productive and referenced ones- and the main lines of research developed, providing a clear and synthetic map of innovation research in family businesses today. This paper approaches innovation from a more theoretical perspective, and also presents the lines of research that are currently being developed. These lines include the internal factors of the family business and its influence on innovation, as well as external factors, among others advances in research in the subject. The paper An Analysis of Open Innovation Determinants: The Case Study of Singapore based Family owned Enterprises, by Koh, Kong and Timperio (2020, this issue) analyzes the drivers of open innovation by studying cases of family businesses in Singapore. The authors highlight the external determinants and catalysts of innovation projects, such as family and business culture, access to external funds, government support for initiatives, market dynamics and partnership between companies. In addition to these six external determinants, there are two other factors that have a great influence on open innovation. First, family capital, which is the main source of financing for innovative initiatives. Second, a strong external network, supported by Singapore's legal and regulatory framework that fosters innovation, promotes the development of an enabling business environment so that the spirit of innovation can truly thrive. Most of the surveyed companies’ managers mentioned process innovation as the most critical aspect, and also organizational innovation. Process innovation is considered superior by the companies included in the sample due to their capabilities to drive product innovation, marketing and organizational structure (and people). Organizational innovation is also considered of utmost importance, due to the need to adopt technologies such as digitalization, robotics or automation, which require an adequate organizational structure. Some ideas from the surveyed managers highlight these statements, like: "The correct processes create the necessary conditions to shape the products, as well as the marketing and organization structures," as well as "Having cutting-edge processes underway is a key differentiator." This study also reflects the need to establish new financing mechanisms adapted to the peculiarities of innovation processes. External capital injection and stimulus policies are necessary, although not sufficient, since they must be combined with the determinants of the internal functioning of family businesses. The relevance of the external network is also highlighted in the paper Collaborative innovation in the family SME: conceptualization, goals, and success factors, by Arzubiaga, Maseda, Uribarri and Palma Ruiz (2020, this issue), which analyzes the strategy of collaborative innovation that seeks the creation of knowledge, new product designs and Improving the efficiency of the production process. Among the conditions of collaborative innovation, four groups stand out: The composition of the management team (in terms of family members percentage and number of generations involved in management), abilities (cognitive factors, absorption capacity and trajectory in innovation), attitudes, and legacy preservation, (referring to socio-emotional wealth and internal behavior). These factors of small and medium family businesses play a crucial role in the successful design and implementation of collaborative innovation. The main contributions of this paper can be summarized in the need for establish solid bases to deepen in the future the study of collaborative innovation. Moreover, a second contribution refers to the identification of the distinguishing characteristics of family SMEs. Arzubiaga, Maseda, Uribarri and Palma Ruiz (2020, this issue) also propose the analysis of the possible moderating effects of firm size and the sector to refine the impact of the variables in this model, looking to achieve excellence in collaborative innovation. As business reviewer, Mr. Osbornehave highlighted collaborative innovation as one of the relevant issues in order to reinforce the role of innovation in their companies. Absorptive capacity is another aspect of great interest to researchers. There are numerous factors that condition it, some of them are features of the family character that make the behavior of family businesses paradoxical (Kotlar et al. 2020). The paper titled A mediating model of innovative capacity between absorptive capacity and family business performanceby Hernández-Perlines, Ariza-Montes and Araya-Castillo (2020, this issue) addresses the issue about absorptive capacity. Absorptive capacity is related to the identification, assimilation and exploitation of new knowledge by the company. Those family businesses that have these capabilities improve their performance. In addition, this effect is enhanced by the innovative capacity of the company, which acts as a mediator between absorption capacity and the company's performance, reinforcing this relationship. Thus, family business managers should focus their efforts on providing their organizations with the necessary skills to absorb and exploit knowledge. This will be easier if the company has developed innovative capabilities. In this sense, the business editor Mr. Gallardo points that: “There is also the possibility of establishing an advisory council with external collaborators that serves as a contrast to the company's board, in which oftentimes the weight of the family is too decisive.” The last two papers in this special issue address the role of family involvement in relation to innovation. Does too much love hinder innovation? Family involvement and firms' innovativeness in family-owned Small Medium Enterprises (SMEs), by Filippo Ferrari (2020, this issue) reflects on the role of family cohesion and its flexibility in the process of innovation, drawing upon the Olson Circumplex model (Olson, 2000) which is applied in a sample of Italian family businesses. The study indicates that unbalanced families show the lowest levels of innovation, although family cohesion and flexibility do not show a significant correlation with the overall level of organizational innovation. Flexibility shows a positive correlation with the process and behavioral innovation, which can be explained by the demand for new forms and organizational routines to deal with process innovation. Here the author suggests some human resources practices that promote flexibility, such as labor rotation (Ortega, 2001), or the development of a horizontal internal career (Ichniowsky et al. 1996, 1997, 1999). Families that lack cohesion show a negative correlation with strategic innovation and process innovation. Ferrari (2020, this issue) considers as disconnected family systems those in which family members are not cohesive and have little family loyalty. On the other hand, innovation in processes is encouraged with new ideas through contributions in terms of new ways of doing things. According to the authors, the Olson Circumplex model (Olson, 2000) offers a framework that can diagnose the extent to which family systems are balanced and how the effects of balanced or unbalanced family dynamics can affect the family business (Daspit et al. 2018). Business reviewers were especially interested on the conclusions of this paper, and also pointed that it would be necessary more research on that kind of negative influences stemmed from lack of cohesion within the business family. Entrepreneurial orientation and product innovation: The moderating role of family involvement in management, by Fredyma, Ruiz Palomo and Diéguez (2020, this issue) addresses a classic concept closely linked to the study of innovation such as entrepreneurial orientation. The relationships between this variable and product innovation, incremental innovation and radical innovation are examined. The influence of family performance on the company is also analyzed. In their conclusions, Fredyma, Ruiz Palomo and Diéguez (2020, this issue) point out that family involvement weakens the positive effect of entrepreneurial orientation in product innovation, especially in case of radical innovation. Therefore, the family business must be aware of these weaknesses to correct them, professionalizing with non-family managers and including their participation in innovation decisions. This conclusion is stressed by both business editors, Mr. Osborne and Mr. Gallardo, who point out that: “Having a network of external collaborators, some of them generalists and others specialized in specific problems, is nowadays practically indispensable.” Finally, the academic editors sincerely appreciate the contributions of two prominent Spanish businessmen, who have contributed to enrich this special issue with a business perspective, which helps to overcome the division that is sometimes perceived between the academic world and the business one. Both Antonio Gallardo and Ignacio Osborne represent the entrepreneurial vision that they have been able to maintain in their families and in their companies for generations. We all know how challenging it is for a family business to be entrepreneurial across generations (e.g., De Massis, Eddleston and Rovelli, 2020). Last but now least, we want to express our gratitude to the editor of the European Journal of Family Business, Professor Vanesa Guzmán for her collaboration and contributions. The Osborne Group, founded in 1772, is one of the oldest family businesses in Europe. The group evolved from the original business of raising and exporting wines from Jerez to a wider food and beverage group which includes quality wines from various Spanish designations of origin, premium spirits, and products derived from Iberian pork, with a growing international acceptance, entering markets as demanding as China. Ignacio Osborne, a member of the sixth family generation, is the current president of the company since 2017, after 21 years as CEO. The company has been especially innovative in marketing, creating the symbol of the bull in the 50s, which has become a symbol that identifies the Spanish, transcending its initial origin as a reference for the winery. Almirall is a pharmaceutical company founded in 1943. It is currently run by the second generation, which are giving way to the third. Although innovation is an essential requirement to compete in pharmaceutics, Almirall has managed to develop some well-known products in Spain, as Almax and Cleboril, becoming one of most innovative companies in the industry. Antonio Gallardo is honorary vice president of his company, which he chaired for 26 years. In addition, he was also president of the Family Council and the Family Office, as well as a member of the Executive Committee of the Family Business Network and vice president of the Family Business Institute.